2020
DOI: 10.3390/pathogens9100834
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of Paecilomyces Penicillatus Provides Insights into Its Phylogenetic Placement and Mycoparasitism Mechanisms on Morel Mushrooms

Abstract: Morels (Morchella spp.) are popular edible fungi with significant economic and scientific value. However, white mold disease, caused by Paecilomyces penicillatus, can reduce morel yield by up to 80% in the main cultivation area in China. Paecilomyces is a polyphyletic genus and the exact phylogenetic placement of P. penicillatus is currently still unclear. Here, we obtained the first high-quality genome sequence of P. penicillatus generated through the single-molecule real-time (SMRT) sequencing platform. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Previous studies reported that a series of soilborne pathogens were able to infect young morel ascocarps that had fructified already ( 8 11 ). In all of these examples, the presence of a single pathogenic strain caused a symptom in the morel ascocarps, consistent with the Koch postulates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that a series of soilborne pathogens were able to infect young morel ascocarps that had fructified already ( 8 11 ). In all of these examples, the presence of a single pathogenic strain caused a symptom in the morel ascocarps, consistent with the Koch postulates.…”
Section: Discussionmentioning
confidence: 99%
“…Possible reasons leading to failure of morel fructification include low vitality of the cultivated strain (the so-called mushroom spawn) used, improper field management practices that provide unfavorable environmental conditions, and soilborne antagonists against the morel. Previous studies reported that the morel was vulnerable to a series of soilborne pathogens ( 8 11 ). The fructification yield of black morel was found to have an association with the community profiles of soil bacteria as well as the physiochemical characteristics of metal elements ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the genome-wide profiles of several species of Morchella, including M. importuna, M. sextelata, and M. septimelata, as well as that of the pathogen P. penicillatus, were reported (Wingfield et al, 2018;Mei et al, 2019;Tan et al, 2019;Wang et al, 2020). P. penicillatus was found to harbor many CAZymes, particularly clusters of chitinase genes, which could be related to its pathogenicity (Wang et al, 2020). Cheng et al (2021) reported the regulatory mechanism of interaction between P. penicillatus and M. importuna.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is analogous to what happened in our present study. Indeed, certain pathotrophic fungal species have proven to inhibit the growth of morel mycelium via antagonistic exudates ( Wang et al, 2020 ). It suggests that growing edible mushrooms relies on multiple microbial interactions, not only between bacteria and fungi ( Carrasco and Preston, 2020 ) but also between microfungi and macrofungi.…”
Section: Discussionmentioning
confidence: 99%
“…Morels cultivated in ordinary farmland soils have been reported to suffer from various soil-borne pathogens ( He et al, 2017 , 2018 ; Lan et al, 2020 ; Wang et al, 2020 ). Besides, morel farmers also reported many cases of severe decreases in morel yield that were suspected as relating to abuse of fungicide, herbicide, and pesticide.…”
Section: Discussionmentioning
confidence: 99%